Echocardiography and Cardiac Rupture: Is Contrast Extravasation an Indication for Surgery?. Issue 1 (24th August 2015) - Katz, Jonathan S.; Heching, Moshe; Hoffman, Darryl M.; Danilov, Tatyana; Tranbaugh, Robert F.
Abstract : Contrast echocardiography demonstrating microbubbles in the pericardial space has often been cited as evidence of ventricular rupture requiring emergent surgical intervention. We report a case where no myocardial perforation was found during post–myocardial infarction surgery despite prior echocardiographic evidence of contrast extravasation into the pericardial effusion. Clinical decision making requires balancing imaging evidence with clinical circumstances to determine the optimal timing for surgical intervention. Mini‐Abstract: Contrast echocardiography demonstrating microbubbles in the pericardial space has often been cited as evidence of ventricular rupture requiring emergent surgical intervention. We report a case where no myocardial perforation was found during post‐MI surgery despite prior echocardiographic evidence of contrast extravasation into the pericardial effusion. Clinical decision making requires balancing imaging evidence with clinical circumstances to determine the optimal timing for surgical intervention.